Current Utilization of Balloon Dilation versus Endoscopic Techniques in Pediatric Sinus Surgery. (November 2014) - Ference, Elisabeth H.; Schroeder, James W.; Qureshi, Hannan; Conley, David; Chandra, Rakesh K.; Tan, Bruce K.; Shintani Smith, Stephanie
Objectives: To study the utilization of balloon catheter dilation (BCD) compared to traditional endoscopic surgery (ESS) in pediatric patients. Study Design: Cross-sectional analysis. Setting: Hospital and freestanding ambulatory surgery centers in California, Florida, Maryland, and New York Subjects: Patients less than 18 years who underwent BCD(316) or ESS(2346), as identified by CPT codes from the State Ambulatory Surgery Databases 2011. Methods: Patient and facility demographics, mean charges, and operating room time were examined using bivariate and multivariate analyses. Results: A total of 2662 children underwent surgery, with BCD used in 10.6% of maxillary, 8.4% of sphenoid, and 11.8% of frontal procedures. Adjusted analysis found that children with asthma, allergic rhinitis (AR), GERD, or concomitant adenoidectomy were more likely to have BCD compared to patients without these comorbidities, asthma odds ratio (OR) = 1.94 (95% CI, 1.84-3.41), AR OR = 1.77 (95% CI, 1.03-3.07), GERD OR = 2.79 (95% CI, .59-4.90), or without adenoidectomy OR = 2.50 (95% CI, 1.84-3.41). Patients with cystic fibrosis were less likely to have BCD, OR = 0.33 (95% CI, 0.11-0.95). Median charges for patients undergoing maxillary antrostomy alone by BCD ( P = .042) or with adenoidectomy ( P < .001) were approximately 2100 and 4200 greater than the median of patients undergoing those procedures with ESS. However, operating room time was similar ( P = .81) between patients undergoing maxillary antrostomy, regardless of whether BCD was used, but was longer ( P < .001) in those undergoing maxillary antrostomy and adenoidectomy when BCD was utilized. Conclusions: BCD was used in 11.9% of pediatric sinus surgery and had higher average charges with no decrease in OR time compared to procedures that only utilized ESS. Future research is necessary to evaluate whether BCD may lead to improved outcomes and eventually decreased operating room time for pediatric patients with chronic rhinosinusitis.